CancerPPD: a database of anticancer peptides and proteins. Issue Volume 43:Issue D1(2015) (30th September 2014) - Tyagi, Atul; Tuknait, Abhishek; Anand, Priya; Gupta, Sudheer; Sharma, Minakshi; Mathur, Deepika; Joshi, Anshika; Singh, Sandeep; Gautam, Ankur; Raghava, Gajendra P.S.
Abstract : CancerPPD (http://crdd.osdd.net/raghava/cancerppd/ ) is a repository of experimentally verified anticancer peptides (ACPs) and anticancer proteins. Data were manually collected from published research articles, patents and from other databases. The current release of CancerPPD consists of 3491 ACP and 121 anticancer protein entries. Each entry provides comprehensive information related to a peptide like its source of origin, nature of the peptide, anticancer activity, N- and C-terminal modifications, conformation, etc . Additionally, CancerPPD provides the information of around 249 types of cancer cell lines and 16 different assays used for testing the ACPs. In addition to natural peptides, CancerPPD contains peptides having non-natural, chemically modified residues and D-amino acids. Besides this primary information, CancerPPD stores predicted tertiary structures as well as peptide sequences in SMILES format. Tertiary structures of peptides were predicted using the state-of-art method, PEPstr and secondary structural states were assigned using DSSP. In order to assist users, a number of web-based tools have been integrated, these include keyword search, data browsing, sequence and structural similarity search. We believe that CancerPPD will be very useful in designing peptide-based anticancer therapeutics.